THE EFFECT OF PAID ADS ON SKINCARE SALES ON FACEBOOK MARKETPLACE - Pakpahan, Arnolt Kristian; Chandra, Kristian; Nilawati, Yuana Jatu (Universitas Muhammadiyah Tangerang, 2024)
Globalization is an event that thins the borders between countries and involves trade, tourism, culture, knowledge, and global relations. This study uses a descriptive qualitative approach, case study, and naturalistic approach, which require humans as research subjects. Facebook failed to attract skincare customers. The results of the interview with users of the skincare product show that they use ordinary unframed photos, which makes the photos look simple and not very appealing. Furthermore, the strategy for writing the posts only uses calls to action (CTAs) without additional elements like location or links that could attract customers. The novelty in this study combines the S-O-R theory with the depth interview technique in exploring the use of social media. The implications of this study are expected to provide marketing managers with a deeper understanding of the influence of paid advertising on product sales.